Incidencia de la autonomía personal, en las actividades básicas de la vida diaria, de los niños con baja visión residentes del instituto especial para ciegos Byron Eguiguren. Periodo 2019-2020 - Acaro Vivanco, Juan Carlos (2021)
The present research work is a documentary review of the scientific literature, depending on the study variables being personal autonomy and the basic activities of daily life, fundamental in the development of the autonomy of children with low vision, it was carried out an investigative design of a descriptive nature, of a bibliographic, argumentative and expository nature, in which information is collected from documents through methods, search strategies and information gathering techniques. Its general objective is to carry out a bibliographic analysis on personal autonomy, to improve the basic activities of daily life. For this, a study of 22 journal articles, 15 theses from digital repositories, 3 books, 15 web pages and 11 documents was carried out, with a total of 66 bibliographic sources. The results showed that personal autonomy affects children with low vision to develop the capacity to carry out the basic activities of daily life, concluding that the child with low vision is able to function on their own and have a autonomous living, through family support and educational agents, as a recommendation, it is necessary to understand the importance of the role played by the family and teachers in the development of autonomy in children with low vision, optimizing and attending to the fundamental needs, giving rise to the proposal of the plan of activities to develop personal autonomy in the basic activities of daily life of children with low vision.